A Made-in-Canada Second Language Framework for K-12 Education: Another Case Where No Prophet is Accepted in their Own Land - Bournot-Trites, Monique Gabrielle; Friesen, Lucas; Ruest, Carl; Zumbo, Bruno D. (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2020)
To ensure quality of education, a language framework should be the foundation on which second language curricula are developed. In 2010, the Council of Ministers of Education, Canada (CMEC), as suggested by Vandergrift (2006a, 2006b), recommended the use of the Common European Framework of Reference (CEFR) in the K-12 Canadian school context and presented several considerations for adaptation before it should be adopted and used. Although the CEFR is partially used across Canada, few of the CMEC’s considerations have been met to date. Given this state of affairs, we suggest the made-in-Canada, Canadian Language Benchmarks and les Niveaux de compétence linguistique canadiens (CLB/NCLC) as an alternative. We argue that the CLB/NCLC, profoundly revised in 2012, best embrace the Canadian context and, using Vandergrift’s criteria for a valid language framework, that CLB/NCLC are now superior to the CEFR in many aspects.